Pola Pengalaman Depresi Perempuan yang Mengalami Kekerasan dalam Berpacaran: Kajian Perspektif Cognitive-Behavioural - Stefanus Perangin-Angin; Sutarto Wijono; Arianti Ina Restiani Hunga (Buletin Psikologi, 2019)
This review aimed to investigate the suitability of therapy derived from Cognitive-Behavioural perspective to be applied as an intervention to treat depressive symptoms in women with dating violence experiences. As this will become a preliminary study to be conducted in Indonesia, a review literature method was employed to gather relevant and up-to-date materials on the topic. Firstly, the issue of dating violence and its urgency in Indonesia were described in the introduction section. In the discussion section, Cognitive-Behavioural perspective and the therapy derived from it, Cognitive Behavioural Therapy (CBT) was described and elaborated in detail. In general, CBT approach was effective in reducing depressive symptoms in women with intimate partner violence (IPV) experiences. As dating violence also belonged to IPV cluster, it is expected that CBT would also become an effective treatment to treat depression in women with dating violence experiences.